Keadilan sebagai Makna Eksistensial: Kritik atas Krisis Normativitas dan Rekonstruksi Paradigma Transformatif dalam Masyarakat Kontemporer - Nadin Oktavia Rasla; Rifqoh El Hanifah; Ratna Malini; Ali Hasan Siswanto; Vina Aulia Hanum (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Discourses on justice in theology, social philosophy, and the humanities have tended to position justice as an ideal normative concept within the structures of law, politics, and social ethics. However, the reality of contemporary society demonstrates various forms of inequality, marginalization, and ongoing structural injustice. This situation raises academic concerns about the gap between theoretical formulations of justice and the existential experience of humankind in social life. Although various studies have addressed the concept of justice in the Islamic tradition and theories of justice in modern social philosophy, most studies still focus on the normative or structural dimension, while the integration of spiritual dimensions, existential awareness, and social transformation remains relatively limited. Thus, there is a research gap in understanding justice not only as a social norm but as an experience of meaning that drives moral action and social change. This article aims to reconstruct the paradigm of justice through an interdisciplinary approach that integrates Islamic theology, moral philosophy, and Viktor Frankl's humanistic-existential psychology, particularly the concept of will to meaning. This research uses a qualitative-conceptual method with a philosophical and hermeneutic approach to relevant classical and contemporary literature. The main argument of this article is that justice can be understood not only as a normative principle within a social system but also as an existential experience rooted in a sense of human meaning and moral responsibility. From this perspective, the spirit of justice functions as an ethical energy that drives individuals and communities to engage in processes of social transformation. The scientific contribution of this research lies in the development of a new conceptual framework that views justice as a transformative existential meaning, thus bridging the normative, spiritual, and practical dimensions in the study of justice. This approach is expected to enrich the interdisciplinary discourse between Islamic studies, social philosophy, and existential psychology in understanding the dynamics of justice in contemporary society.